Evaluating the Growth Potential of Halal Tourism in Palu - Sitti Aisya; Nur Syamsu; Muthmainnah. MD (Institut Agama Islam (IAI) Al-Qolam, 2023)
Indonesia possesses significant potential in halal tourism, but Palu city has yet to fully utilize its resources despite its abundant natural, cultural, and historical wealth. This research used qualitative method that analyzes the successful halal tourism industry in Lombok as a benchmark. The analysis indicates that Lombok's success in developing halal tourism can be attributed to active community participation, a business model prioritizing societal welfare, and full support from the local government. Key implications from this study include engaging the local community, active support from local authorities, effective promotional strategies, and broad collaboration within the surrounding regions. Implementing best practices from successful halal tourism destinations is expected to accelerate the growth of the halal tourism industry in Palu City, ultimately leading to positive impacts on economic growth. Future studies should focus more on preferences, social and cultural aspects, innovative marketing strategies, collaboration with local communities, and adopting best practices aligned with local values and culture.